IMPLEMENTASI MUATAN LOKAL PENDIDIKAN DINIYAH DALAM PENINGKATKAN MUTU PENDIDIKAN AGAMA ISLAM : (Studi di SDN Keras 2 Diwek Jombang) - Sodikin, Ahmad; Nasuhah , Zainun (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
Early Education is a branch of science that applies teaching classical or modern as well as efforts to instill Islam as part of the foundation of students' lives to produce famous ulama' who not only understand science, but also have broad religious insight, and horizons of thought as a form of solving problems in society.The purpose of this research is to describe the implementation of the local content of diniyah education in ncreasing the religious understanding of students at SDN Keras 2 Diwek Jombang, describe the increase in religious understanding of the results of grade 1-VI students. In this study, the researcher used a qualitative descriptive research method. While the data collection methods used are: observation, interview, documentation. The results of this study are: 1) The implementation of local content for diniyah education at SDN Keras 2 Diwek is going very well, all matters related to diniyaheducation are structured. The teachers use interesting learning methods at the time of learning so that students do not get bored easily, there are facilities from the school in the form of a yellow book, a report card of student learning outcomes forone year. 2) The inhibiting factors faced in the implementation of diniyah education are as follows: a) The main obstacles when learning diniyah students are still having difficulty understanding Arabic pegon lessons. b) for students there is a lack of support from parents due to the limited knowledge of each parent. c) during the learning process, many teachers and students were hampered by the time signal during the pandemic and the use of less than optimal learning methods. 3) Evaluation of Diniyah education is seen from the average daily test scores (UH), Mid-Semester Assessment (PTS) and Final Semester Assessment (PAS).